Standardization of good agricultural practices (GAP)in kacholam (Kaempferia galanga L)for yield and quality - Chandana R (Department of Plantation crops and spices,College of Horticulture, 2011)
An investigation on “Standardization of good agricultural practices (GAP) in kacholam (Kaempferia galanga L.) for yield and quality”, was carried out at the Department of Plantation Crops and Spices, College of Horticulture, Vellanikkara, during 2010-2011 to standardize organic resource management and post harvest handling practices in kacholam for optimizing yield and quality, leading to formulation of good agricultural practices in the crop. Results of the study revealed that the treatments which included FYM along with biofertilizers proved superior in terms of earliness in germination whereas FYM supplemented with Kalanchoe pinnata recorded the maximum germination percentage of 98.61 and all other treatments were on par. Plants which receive FYM along with biofertilizers recorded the maximum leaf number (30.67) at 6 MAP. Vermicompost supplemented with kalanchoe and FYM enriched with biofertilizers recorded the highest values for foliage spread at later stages of crop growth. In the present study, the superiority registered by the control plots receiving inorganic fertilizers with respect to vegetative growth parameters at early stages of growth was not evident at later stages. Experimental plots applied with FYM enriched with biofertilizers recorded the highest value for fresh rhizome yield per plant (80.30 g) and fresh (9.93 t ha-1) as well as dry (3.19 t ha-1) rhizome yields per hectare, which were on par with the rest of the treatments. Plots incorporated with FYM and kalanchoe, recorded significantly higher values for dry recovery (36.4 %). Control plots applied with inorganic fertilizers recorded the lowest dry recovery percentage (31.42 %) as well as dry rhizome yield (2.32 t ha-1). Essential oil content was significantly higher in plots applied with FYM supplemented with kalanchoe (1.47 %) and oleoresin content recorded a significantly higher recovery percentage of 3.42 per cent in plots applied with FYM supplemented with kalanchoe and biofertilizers. Control plots which received inorganic fertilizers recorded the least recovery of essential oil (0.87 %). FYM supplemented with kalanchoe, singly and along with biofertilizers and chromolaena mulch, recorded highest available P (92.48 kg ha-1) and N (503.8 kg ha-1) content in soil respectively. Vermicompost supplemented with kalanchoe recorded high content of soil K and all other treatments were on par. Control plots registered the lowest soil K content. Higher plant uptake of major nutrients was observed in vermicompost treated plots. Enhanced population of soil microbes was recorded by the use of organic nutrients and biofertilizers. FYM supplemented with biofertilizers and vermicompost applied singly and along with kalanchoe and biofertilizers recorded the maximum bacterial, fungal and actinomycetes population. During the course of experiment, maximum incidence of bacterial wilt was observed in FYM manure received plots. Composite samples of kacholam registered no significant variation in dry recovery during sun drying, shade drying and oven drying. Maximum quality constituents were retained in sun dried samples of the crude drug, recording 1.2 per cent essential oil and 3.4 per cent oleoresin though the variations were not significant. Storage studies revealed the least percentage loss in weight (0.98 %) and residual moisture content (6.78 %) in samples stored in polyethyleneterephthalate (PET) bottles, at 6 months after storage. Essential oil and oleoresin contents recorded the maximum values during storage in PET bottles and polyethylene bags respectively. Samples stored in polyethylene bags and PET bottles did not record any insect infestation and had registered minimum microbial infection. Percentage loss of essential oil and oleoresin ranged from 5-30 per cent and 22-55 percent depending on method of storage.